The Present and Future Definition of Health Insurance Based on Laws and Regulations in Indonesia - Dewi Probo Astuti; Clara Meilindawaty Situmorang; Sri Evehulisa Pinem; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
This study analyzes the legal principles that Indonesia insurance plays an important role in facing increasingly complex and uncertain life needs. In Indonesia, insurance is regulated through Law No. 40 of 2014, which provides a legal basis for the implementation and protection of the parties. This study uses a literature study method with a qualitative narrative synthesis approach to examine the definition of insurance based on laws and regulations in Indonesia. First, to analyse the legal basis of insurance and the legal aspects of the implementation of insurance agreements in Indonesia, examine the legal principles underlying the implementation of insurance practices in Indonesia, also evaluate the legal challenges in the implementation of insurance practices in Indonesia and provide recommendations and efforts for improvement in the insurance sector in Indonesia. Secondly, to analysis of the legal basis and implementation of insurance agreements shows that the legal framework for insurance in Indonesia is quite complex. Various challenges are still found in its implementation, such as complex regulatory changes, suboptimal consumer protection, and problems related to insurance claim disputes. We propose several recommendations and improvement efforts namely by improving regulations, and increasing supervision of law enforcement by the OJK, transparency and public education, and increasing cooperation between insurance companies, the OJK, and dispute resolution institutions. These efforts are important to realize an insurance system in Indonesia that is fair, inclusive, transparent, and sustainable from present to the future.